PENGARUH BIAYA OPERASIONAL, JUMLAH PERPUSTAKAAN, DAN TEKNOLOGI DIGITAL TERHADAP PRODUKTIVITAS PUSTAKAWAN DI PERGURUAN TINGGI : : STUDI KASUS PADA JUMLAH MAKALAH PUSTAKAWAN YANG TERBIT - Adi, Prasetyo (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
Publications can be a tool for librarians to develop and refine their skills. College libraries aim to assist academics in conducting research. Librarians must master a particular field to write papers, so they can assist teachers. There are many obstacles for librarians to be productive through publications. This study aims to analyze whether the number of libraries, total library operational costs, and the number of digital devices in library services affect the number of papers written by librarians. This study uses secondary data on libraries in the provinces of East, West, and Central Java, from 2018-2022. The data is in panel form and was analyzed using the Random Effect Model through Eviews software. Before being analyzed, the data was first tested with the classical assumption test to determine the normality of the data and the Chow and Haussmann tests to determine the appropriate panel analysis model. The results show that operational costs for libraries and the number of digital devices used for library facilities have a significant effect on librarian productivity in writing papers. However, the number of libraries in a province does not have a significant effect on the number of papers produced by librarians.